PENGARUH GOOD CORPORATE GOVERNANCE DAN TEKNOLOGI PADA KINERJA SISTEM INFORMASI AKUNTANSI LPD KOTA DENPASAR - Ni Luh Nyoman Sherina Devi; Ida Ayu Ratih Manuari (UNHI Press, 2024)
The aim of this research is to evaluate and collect empirical data regarding the impact of good corporate governance on the relationship between technological sophistication, user capabilities, training and education on the performance of accounting information systems at Lembaga Perkreditan Desa (LPD) in Denpasar City. LPD is a unique financial institution that exists only in Bali, Indonesia. The population is LPD in Denpasar City, and purposive sampling technique was used to select 34 LPDs as samples. Documents and questionnaires were used to collect data, which was then analyzed using the partial Least Square (PLS) method using SmartPLS 3.0 software. The results showed that technological sophistication, user capabilities, also training and education have a positive and significant effect on the performance of accounting information systems in LPDs in the city of Denpasar. Furthermore, there is evidence that good corporate governance strengthens the relationship between technological sophistication, user capabilities, and training and education with the performance of accounting information systems. These results underline the importance of implementing good corporate governance to improve efficiency and competitiveness through better accounting information systems.